Pengaruh Good Corporate Governance, Tekanan Pemegang Saham, dan Umur Perusahaan terhadap Kualitas Sustainability Report - Yuliandhari, Willy Sri; Citta, Nandini (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
The quality of the sustainability report shows that the company is responsible and helps stakeholders understand and make decisions. Sustainability reporting is a tool or vehicle for companies to report and communicate environmental, economic and social aspects to their stakeholders. All reports issued by the company must be of high quality. This study aims to determine the simultaneous and partial effects of good corporate governance, shareholder pressure and company age on the quality of sustainability reporting. The subjects of this research are companies in the food and beverage manufacturing sector that are listed on the Indonesia Stock Exchange for the 2018-2021 period. The sampling technique used was purposive sampling. The research sample consisted of 80 observational data. Analysis of research data by panel data regression using the Eviews 12 application. The results of this study indicate that shareholder pressure has a significant positive effect on the quality of corporate sustainability reporting. Good corporate governance and company age have no effect on the quality of sustainability reports. Based on the results of this study, companies can improve the quality of their sustainability reports according to GRI standards and investors should consider sustainability reporting as one of their personal criteria. Future researchers will be able to use other independent variables or use different proxies for these variables and can also choose different research subjects. Keywords: good corporate governance, kualitas sustainability report, tekanan pemegang saham, umur perusahaan,